Democracy and development : the case of Guyana - Andaiye (WAND St. MichaelBB, 1995)
Describes a number of deformations in Guyanese society and shows how they developed out of a particular post-World War 2 history. Suggests that this social legacy of the post-World War 2 history is impeding the functioning of representative government, preventing the democratising of power through the society, and therefore is acting as a major barrier to development.